Implementing experiential learning logs addressing social accountability into undergraduate medical clerkship education (Canadian Medical Education Journal, 2022)
Implication StatementMedical schools have a responsibility to ensure students meet and advocate for the needs of the community. However, addressing the social determinants of health is not always emphasized in clinical learning objectives. Learning logs are useful tools that can engage students to reflect on clinical encounters and direct students in their learning to target the development of highlighted skills. Despite their efficacy, the use of learning logs in medical education is largely applied towards biomedical knowledge and procedural skills. Thus, students may lack competence to address the psychosocial challenges involved in comprehensive medical care. Social accountability experiential logs were developed for third year medical students at the University of Ottawa to address and intervene on the social determinants of health. Students completed quality improvement surveys and results demonstrated this initiative to be beneficial to their learning and contributed to greater clinical confidence. Experiential logs in clinical training can be adapted across other medical schools and tailored to fit the needs and priorities of each institution’s local communities.